Administração sistêmica de agentes poliaminérgicos modula a memória na tarefa de medo condicionado em ratos - Camera, Keli (2006)
The polyamines, spermine, spermidine and putrescine, are a group of aliphatic amines that interact with diverse cellular targets such as nucleic acids and proteins. The polyamines may act as physiological modulators of N-methyl-D-aspartate (NMDA) receptors. The processes mediated by NMDA receptor include synaptic plasticity and formation of neural circuitry consequently in the learning and memory process. However, little is known about the role of systemic administration endogenous modulators of the NMDA receptor, such as polyamines, in Pavlovian fear conditioning learning. In this paradigm, an emotionally neutral conditioned stimulus (CS), such as a tone, elicits behavioral responses after association with a noxious aversive unconditioned stimulus (US), such as a brief electric footshock. Once the CS-US association is learned, innate physiological and behavioral responses appear, such as freezing. Therefore, the present study was conducted to investigate whether the immediate post-training intraperitoneal injection of spermidine (1-100 mg/kg), an agonist of the NMDA receptor polyamine binding site, arcaine (0-360 min post- training), an antagonist of the NMDA receptor polyamine binding site and/or MK-801, a noncompetitive antagonist of the NMDA receptor, affected classical fear conditioning in rats. Intraperitoneal administration of arcaine (10 mg/kg) decreased, within a limited time window (0-180 min post-training), while spermidine (10-100 mg/kg) increased contextual and auditory fear conditioning. Arcaine or MK-801 co-administration, at a dose that had no effect per se, reversed the facilitatory effect of spermidine. These results provide evidence that endogenous and exogenous systemic administration of polyamine binding site ligands modulate early consolidation of fear-conditioning task. The facilitatory effect induced by spermidine would be NMDAreceptor-mediated.